Adolescent Communication Pattern in Digital Era - Masril, Munzaimah (Universitas Medan Area, 2018)
Communication as a process of information dissemination also changes along with technology developments that occur. Instant, is a feature of a digital era, where speed becomes everything and can simultaneously provide good and risk for its users. Technology development also changes the way humans interact with one another, by eliminating face-to-face communication. This situation also causes changes in values, ways of thinking, and human behavior in addressing their lives, especially among adolescent. Communication patterns that are built between adolescent and those around them, for example with peers and parents also experience changes in terms of quantity and quality. This research was conducted at the University of Sumatera Utara with a total of 400 respondents and using a questionnaire. This is a quantitative descriptive research that produces an overview of the application of short messages used by teenagers in interacting with a family. The results also illustrate the communication patterns that occur with the use of short message applications in interacting with family members.